FIXED COMBINATIONS IN ACHIEVEMENT TARGET LEVEL OF BLOOD PRESSURE IN PATIENTS WITH ARTERIAL HYPERTENSION. (April 2021) - Rekovets, Oksana; Sirenko, Yuriy; Torbas, Olena; Kushnir, Svitlana; Primak, Galina; Sirenko, Olexandr; Krushynska, Nina; Ponomareva, Galina
Abstract : Objective: Aim. Evaluate the therapeutic efficacy of fixed triple combination of valsartan / amlodipine / hydrochlorothiazide compared a double fixed combination of valsartan / amlodipine in patients with arterial hypertension. Design and method: The study included 50 patients with moderate and severe arterial hypertension. Patients were divided into 2 groups. The first group (n = 25) received fixed triple combination of 160 mg valsartan / 5 mg amlodipine / 12.5 mg hydrochlorothiazide once daily, in the morning for 1 month. Patients in the second group (n = 25) received a double fixed combination of 160 mg valsartan / 5 mg amlodipine once a day, in the morning for 1 month. If necessary, dose was titrated to 320/10 / 12.5 mg (valsartan / amlodipine / hydrochlorothiazide) or 320/10 mg (valsartan / amlodipine). After 3 months of treatment was control of therapy. Results: The average age of patients 54.9 ± 1.8 (25–75) years, BMI 31.2 ± 0.7 kg / m2. Office SBP/DBP at the beginning 161.7 ± 1.8/98.5 ± 1.4 mmHg, HR 70.7 ± 1.4 beats / min. 24 SBP/DBP 143.8 ± 1.1/92.4 ± 1.2 mm Hg. 24HR 71.5 ± 1.5 beats / min. The decrease 24SBP/DBP was 18.0 / 16.1 mm Hg (p < 0, 05) on (val/aml) and 23, 8 / 20, 7 mm Hg (p < 0, 05) on (val/aml/HTZ). The decrease day time SBP/DBP - 19.4 / 17.8 mm Hg (p < 0, 05) on (val/aml) and 17, 8 / 22, 6 mm Hg (p < 0, 05) on (val/aml/HTZ). Decrease mean nocturnal SBP/DBP 17.0 / 12.1 mm Hg (p < 0, 05) on (val/aml) and 20, 5 / 18, 2 mm Hg (p < 0, 05) on (val/aml/HTZ) combination. Achievement of target BP at ABPM was 77.3% - in the double (val/aml) combination and 95.2% in the triple (val/aml/HTZ) combination. Conclusions: The triple fixed combination (val/aml/HTZ) was more effective in reducing blood pressure with daily monitoring compared to a double fixed (val/aml) combination which was not increase in side effects.